Peranan Pemimpin dalam Lembaga Pendidikan Islam, Lembaga Tahfidz Qur’an Al-Bayyinah - Nur Khalizah; Cinta Taufika; Amalia Maypida; Nurul Fatwa (Departement of Mathematics Education, 2023)
The purpose of this article is to describe the role of the chairman or head of an institution in the field of Islamic education, namely an institution for memorizing the Al-Qur'an as a leader in the institution. The data for this article were collected through interviews, documentation and observation and the subject of this article was the head or head of the Tahfidz Qur'an Al-Bayyinah institution. The results of this study indicate that the head of the institution has a role as a leader in the process of running the institution he manages. The hostel leader or head of the hostel has full responsibility for his success in educating students, because the head of the hostel will be held accountable based on his performance both in this world and in the hereafter.